Dissertações e Teses. - Buss Cezar, Gustavo; Pivetta de Mello, Veridiana; Baptista Reis, Pedro Henrique; Claser Elmi, Alexandre; Crispim da Fontoura, Marcelo; Canatta de Souza, Fábio; Prado Furuzawa, Camila; Fischer Cunha, Emiliano; Leal Pereira, Monalisa; Mendes Pereira, Guilherme; et al. (Revista FAMECOS, 2014)
-